The Public Years of Sarah and Angelina Grimké Selected Writings 1835–1839 - Ceplair, Larry 1943- (Columbia University Press, 1989)
Looks at selected writings from Sarah and Angelina Grimke from 1835-1839. The sisters were considered revolutionaries who blazed a path for women of courage who believed in social change and activism